Rencana Aksi Pelayanan Berkesinambungan Rawat Jalan dalam Rangka Meningkatkan Citra RSUP Fatmawati - Attas, Andi Wahyuningsih (UI Scholars Hub, 2014)
This study aims to identify the continuous action plan in Fatmawati General Hospital outpatient services in order to increase the Fatmawati General Hospital’s image. The study is conducted through interviewing patients, health workers, managements staff, and the macro analysis is done through policy analysis. The results showed that thegap in outpatient service is in the compatibility quality (service speed, drug completeness, comfort) and communication. The dissatisfaction occured in Fatmawati General Hospitals is the cultivation of the main root problem which is the rising numbered of patients as a result of the referral system ineffectiveness. The action plan designed in a macro scale is to improve the referral system with a focus on balancing the role of public health unit and the individual health unit and in the micro scale the action plan is conducted through out hospitals internal improvements. This efforts also needs to be strengthened through Primary Health Care System as a strategy to ensure the affordability of essential health services provided universally to the public in order to achieve the common goal of better health.